Reading Habits from the Perspective of Diverse Socioeconomic Status - Holidiya, Hani; Putra, Bambang Arya Wija; Tasnim, Zakiyah (English Education Study Program, 2024)
Research has presented different results on students’ reading habits concerning their socioeconomic status. The present study focuses on reading habits regarding the socioeconomic status of Indonesian EFL students to examine whether socioeconomic status represents students’ reading habits. An online survey was conducted to observe the EFL students, followed by descriptive analysis to examine the data. This study categorizes students’ socioeconomic status and reading habits level into three categories, namely high, middle, and low, to enable the researcher to determine whether there is a correlation between the two aspects. Based on the data gathered from the survey, it is found that students’ reading habits are not always inferred by their socioeconomic status. Among 230 participants, 27% were from high socioeconomic status families, 59% of the students were from middle socioeconomic status, and the remaining 14% were from low socioeconomic status. Besides categorizing students’ socioeconomic status, this research found that even students with the same socioeconomic status have various reading habits. Further research on reading habits among siblings is suggested to gain more detailed information on whether socioeconomic status represents students’ reading habits.